Witness through holiness of life: A quick look into the biography of a concept - Siladi, Paul (Diakrisis, 2021)
"Witness through holiness of life" is a phrase often used in theological texts. This study analyses the origin of this concept and identifies a series of reference points in its intellectual biography in Romanian theology (with special emphasis on the developments brought about by mission theologians from Cluj-Napoca). The two final sections try to enlarge upon the reflection on the witness through the holiness of life by considering the phrase in a biblical and spiritual context.